Pemberian Opioid Sebagai Manajemen Nyeri pada Pasien Pediatrik - Sari, Djayanti; Sudadi; Hanafi, Irham (Jurnal Komplikasi Anestesi, 2019)
Pain is a complex phenomenon that occurs due to the transmission of nociceptive stimuli from the peripheral nervous system through the spinal cord to the cerebral cortex. Given the complexity of the pain mechanism, effective treatment of pain requires the use of multimodal therapies that target multiple sites along the pain pathways. Opioid receptors decrease the release of excitatory neurotransmitters from terminals carrying nociceptive stimuli.The use of opioids in the management of acute pain in children must be considered when the intensity and the duration of the pain does not respond to the other classes of analgesic drugs. The increase in the knowledge of physiologic and pharmacologic of these medications has reduced the fear of their application in the pediatric field and helped in the recognition and management of side effects, where excessive sedation and severe respiratory depression are the most serious adverse effects of opioids.